Sign Language Interfaces: Discussing the Field's Biggest Challenges - Bragg, Danielle; Morris, Meredith Ringel; Vogler, Christian; Kushalnagar, Raja; Huenerfauth, Matt; Kacorri, Hernisa (2020 CHI Conference on Human Factors in Computing Systems, 2020)
Sign language interfaces offer rich, timely research problems. Recent advances in computational methods have made a wider range of sign language interfaces possible. At the same time, a recent interdisciplinary review and call-to-action outlines the most pressing challenges for the field, given these recent advances. This special interest group (SIG) will meet to discuss and make progress along these challenges, providing continuity for researchers working in this space, while exchanging ideas with the broader HCI research community.